The Role of Religious Teachers in Internalizing Religious Moderation Values for Children with Special Needs - Nadlifuddin, Mohammad Ilham Nadlifuddin; Mohammad Khoirur Rozaq; Tri Andita Noviana (Jurnal Pendidikan Islam, 2025)
Religious moderation is crucial for fostering tolerance and preventing extremism in diverse societies, including among children with special needs. This study analyzed the role of religious teachers in internalizing Religious Moderation Values at Kaliwungu State Special School, Kudus. A descriptive qualitative approach was employed in this research. Data were collected through non-participant observation and in-depth interviews with teachers actively involved in teaching students with special needs. The findings showed that teachers acted as instructors, facilitators, and role models in cultivating Religious Moderation Values. Applied teaching methods included experiential learning, storytelling, the use of visual media, and a reward system to help students understand and practice values such as tolerance, mutual respect, and peaceful coexistence. The study also identified various challenges, such as differences in students' cognitive abilities, emotional instability, and communication barriers. However, these challenges were overcome through curriculum adaptation, tailored teaching strategies, and active collaboration with parents.